Tingkat Kepuasan Parkir Kampus Anggrek Binus University Ditinjau dari Fasilitas Geometri dan Survei Kepuasan Parkir - Irpan Hidayat (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Evaluated from the level of saturation, Anggrek Campus Binus University facilities are considerably able to accommodate all vehicles to park. However, from observations over the years, even though the capacity still seems able to accommodate, there are still some drivers who have difficulty in placing their vehicle in the provided parking lots. In results, it take a long time for drivers to do the maneuvers. Due to this reason, there is a need to review the geometric conditions of a parking space and user parking satisfaction at Anggrek Campus. The research method is to conduct a survei for the parking geometry in a questionnaire form, which aims to determine the satisfaction level of the parking facility from the user side. The research results acquired for parking plot 4000 x 2400 mm, the type of vehicles that meet the requirements of free space to park in the lateral direction of the plot is city car, jeep, and MPV. As for the parking plot 5000 x 3000 mm, free parking space requirements for the lateral direction meet for all types of vehicles (city car, jeeps, MPV, sedans, and SUVs). Results stated that 39% of respondents are comfortable in terms of ease of parking, 37% of respondents express comfort in opening the car door after parking their vehicle, 24% said parking signs are very useful for them in getting the parking information. However, 22% of respondents expressed their discomfort in the ease of parking due to the geometry of 90° parking pattern.